Photodegradation Performances Of Low-Density Polyethylene Composites Loaded With Photocatalysts - Sutanto, Nelvi (2019)
Growing production and consumption plastic worldwide is currently resulting in a significant solid waste and is causing serious pollution problems. Various approach has been attempted and photodegradation seems to be the environmental benign approach. However, the degradation rate that has been achieved is only in the range of 0.03 to 0.21 %/h. Therefore, in this work, an appropriate photocatalyst that could expedite the photodegradation rate of the polymer was developed based on zinc oxide (ZnO), titanium dioxide (TiO2) and graphitic carbon nitride (g-C3N4) by sol gel method. The effect of ZnO/TiO2 ratio and wt% of g-C3N4 was investigated. The best photocatalytic activity performed by photocatalyst ZnO/TiO2 with ratio of 3:1 that was incorporated with 10 wt% g-C3N4 denoted as 10C-3ZT was selected to fabricate LDPE composite films. The optimized photocatalyst is 10C-3ZT with following features: dominated by zincite phase and minor traces of c-Zn2Ti3O8 together g-C3N4, formation of heterojunctions within ZnO/g-C3N4 and c-Zn2Ti3O8/g-C3N4, mixture of spherical and rod shape particles, low band gap energy of 2.5 eV have remarkable reduced recombination of e-h in 10C-3ZT photocatalyst thus resulted in 99% degradation within 45 minutes with kinetic rate constant of 0.093 min-1. LDPE composite films with 3 different thickness (1 mm, 0.1 mm and 0.035 mm) was prepared with 10C-3ZT. Compression moulding was used to produce 1 mm composite films and wet casting method for films with 0.1 and 0.035 mm thickness. The weight % of 10C-3ZT was varied from 1 to 10 wt% and the properties of LDPE/10C-3ZT composite films were compared with pure LDPE by analysing the changes in weight loss, carbonyl index, tensile strength, percentage elongation, morphology, chemical structure, degree of crystallinity. The weight loss was further enhanced with 10 wt% PVA functionalized photocatalyst (10C-3ZT-10 wt%-PVA) in LDPE polymer matrix. The total weight loss of 96% was attained in 350 h. Carbonyl index up to 2 was achieved. Enhanced OH• released due to heterostructure formation, increase in amorphous region and PVA functionalization for water absorption resulted in substantially improvement in degradation of LDPE, which was 47 times faster than pure LDPE.